Pengaruh Biaya Tenaga Kerja Langsung dan Kos Barang Terjual terhadap Sticky Costs pada Perusahaan Manufaktur (International Forum of Researchers and Lecturers, 2023)
This research aims to determine the sticky costs behavior that occurs in manufacturing companies listed on the Indonesia Stock Exchange. The behavior of sticky costs in this research is seen from sales, general and administration costs which are categorized into several industry groups to see the degree of sticky costs for each industry group per year. Apart from that, the factors that influence sticky costs include direct labor costs and overhead costs. goods sold. The research method used is multiple linear regression analysis which is measured using the Anderson, Banker and Janakiraman equations. The sample was determined based on the purposive sampling method with a total of 65 research samples obtained during the 2017-2019 period. The results of this research are that all manufacturing companies in Indonesia have sticky costs behavior. The largest and smallest degrees of sticky costs occur in the textile, garment and footwear sectors and others. This proves that management in companies in these sectors is inconsistent in monitoring and controlling sales, general and administrative costs. Then regarding the influence of direct labor costs and the cost of goods sold is as follows: 1) Direct labor costs have no effect on sticky costs, 2) Cost of goods sold has no effect on sticky costs.